Simulation on heat transfer performances of hollow tube electric heaters with dual-side longitudinal flow. Issue 7 (22nd February 2020) - Mei, Xianzhi; Chen, Yaping; Wu, Jiafeng; Zhou, Xiaoyu
Abstract : Purpose: Conventional electric heaters mostly use U-shaped electric heating tubes and the hollow tube electric heaters are new type ones that rely on the heat transfer tubes as heating elements. However, in the original design, the fluid flows through the annular gaps between the shell wall and the supporting plates, the chambers between supporting plates are generally stagnant zones. The purpose of study is to overcome these deficiencies. Design/methodology/approach: A modified approach is proposed in which the heating tubes are surrounded by holes on the supporting plates, thus the stagnant flow zone can be eliminated and the heating surfaces of both inside and outside the tube can be fully used. Numerical simulations were carried out on four schemes of hollow tube electric heaters, i.e. plate blocked, countercurrent, parallel and split. The results show that the two schemes of parallel and split can reduce the temperature difference between the two sides of the fixed tube plate, and thus reduce thermal stress and prolong the service life. Findings: The split scheme of electric heater has the highest comprehensive index, moderate heat transfer coefficient and minimum pressure drop on the shell side. Its average heat transfer coefficient and comprehensive index are, respectively, 15.7% and 52.9% higher and its average pressure drop and tube wall temperature are, respectively, 57.6% and 19 K lower than those of the original plate blocked scheme, thus it can be recommended as the best scheme of the hollow tube electric heaters. Originality/value: Based on the original design of hollow tube electric heater with plate blocked scheme, three plate perforated schemes were proposed and investigated. The thermal and flow features of the four schemes were compared in terms of heat transfer coefficient, pressure drop and comprehensive index h o ·Δ p o −1/3 . The split scheme can reduce the temperature difference between two sides of the fixed tube plate with reduced thermal stress. It has moderate tube wall temperature and heat transfer coefficient, the smallest shell side pressure drop and the highest comprehensive index h o ·Δ p o −1/3, and it can be recommended as the optimal scheme.